### Math MCQ - English

# If the roots of the equation (b - c)x2 + (c - a)x + (a-b) = 0 are equal, then

Home | Discussion Forum** If the roots of the equation (b - c)x2 + (c - a)x + (a-b) = 0 are equal, then**

2b = a + c

a = b = c

b2 = ac

none of these

Answer : A

** View More Related Question**

** 2) The sum of the first ten terms of an AP is four times the sum of the first five terms, then the ratio of the first term to the common difference is**

** 3) If the first term of an AP is 2 and common difference is 4, then sum of its first 40 terms is**

** 4) The sum of 5 numbers in AP is 30 and sum of their squares is 220. Which of the following is the third term ?**

** 5) 1,8,15,22,29,36,… is**